Variability and structure of the costs of purchasing district heating for three selected groups of users in 2019-2024 - Bartnicki, Grzegorz; Nowak, Bogdan (Instal, 2025)
This article presents the results of the analyses of the purchasing district heating cost by the final recipient (housing co-op regulated in the Polish law) for three different groups of recipients (groups of residential buildings for which heat is generated in separate heating plants of the same heating system in one of the cities of southwestern Poland), in the period from 2019 to 2024 (2024’Q3). This heating system is small and has several separate heat sources. During this time, in 2020 the COVID-19 pandemic broke out, in 2022 the troops of the Russian Federation entered Ukraine (and there is a full-scale war going on for over 1000 days), there were unprecedented record increases in the price of steam coal on world markets and in Poland. In Poland, from 2022, regulations were introduced to protect households and selected recipients of heat, gas fuels and electricity from excessive cost increases (so-called anti-inflation shield [21]). The article describes changes in the costs of purchasing heat and the share of individual components in this cost.